Analysis of The Causes of Failure to Blow 600 ml Bottles on Blow Molding Machine with The Fishbone Diagram - NurSalam, Syahlan; Erwin, Erwin; Ilmi, Bahrul (Universitas Sultan Ageng Tirtayasa, 2023)
Failing Blowing is an imperfect preform blowing process. The defective form can be a puckered preform, a leaking bottle or a puckered bottle. Blowing failure is influenced by three main parameters, namely preform, preblow and blowing temperatures [1]. Then data was taken with variations of the material used, namely preform materials from internal and external. This is not intended to assess the effectiveness of the amount of production using a particular material, but makes a reference in analyzing the problem of failed blowing with different material variations. The analysis stage is carried out using the fishbone diagram method. The results of the analysis found the cause of blowing failure and a significant difference in numbers from the blowing failure data taken on internal and external preforms. The main possible causes of failure to blow settings are inappropriate parameters. The number of blowing failures in internal materials was obtained as many as 23 and in external materials as many as 8 bottles. Then the main parameter settings used in internal materials with a preform temperature of 107oC, a preblow pressure of 6.7 bar and a blowing pressure of 22 bar. While in external materials the preform temperature is 106oC, the preblow pressure is 6.7 bar and the blowing pressure is 22 bar. Looking at the type of material alloy of internal and external preform, this has a difference where the external preform is a preform with 100% PET (virgin) resin while the internal preform is a combination of 25% Recycle PET and 75% PET. This will obviously greatly affect the characteristic properties of the material.